Merger Bank Syariah dan Pengembangan UMKM di Indonesia - Muhammad Rauuf Ramadan (Jurnal Syntax Transformation, 2021)
Sharia Banks are financial/banking institutions whose businesses and products are developed under the provisions of Sharia law, especially the procedures for converting in Islam. The merger is a legal action carried out by one or more companies to merge with another existing company which results in the assets and liabilities of the merging companies being transferred by law to the company that accepts the merger and subsequently the legal entity status of the merging companies ends by law. . The merger of Islamic banks also encourages the growth and development of the MSME sector. The purpose of this study was to determine the effect of Islamic banking mergers on various employees, shareholders, and customers as well as the role of Islamic banking in encouraging the economy of MSME actors during the Covid-19 Pandemic. The research method used in this study was descriptive qualitative and used secondary data sources from several works of literature such as journals and books related to the issues being discussed. The results of the study are that the Sharia Bank Merger Policy has an influence on employees, shareholders, and customers as well as in the development of MSMEs in Indonesia. Islamic banks provide financing to MSME participants in the form of working capital so that with these funds existing sectors in society can be increased to meet community needs. The presence of Islamic banks and financial technology (Fintech) companies in MSME financing is expected to provide positive things for growth